Jiang, L., Wu, L.F., Huang, G.Y., He, B.S., Yu, J.R. & Xu, K.W. (2020) A new species of Ilex sect. Ilex (Aquifoliaceae) from Guangdong, China. Phytotaxa 428 (2): 153–158. - Jiang, Lei; Wu, Lin-Fang; Huang, Guan-Yun; Yu, Jia-Rong; He, Bi-Sheng; Xu, Ke-Wang (Phytotaxa, 2020)
N/A